Does board diversity affect Corporate Social Responsibility in Sri Lanka? - Pratheepkanth, P.; Arulvel, K.K. (University of Jaffna, 2020)
paper aims to examine the impact of board diversity on corporate social responsibility (CSR) in Sri Lanka. This study uses quantitative techniques to assess the board diversity and CSR of Sri Lankan firms. A 100-firms sample, randomly drawn from the Colombo Stock Exchange (CSE)-listed firms. Secondary data for the financial year 2017/18 are obtained from the CSE databases and are used to calculate the board diversity and CSR for the sampled firms. It is found that the diversity of board resources positively affects CSR. Diversity of board may encourage companies to invest in CSR, which will enhance the image of their companies. The study also proves a positive effect of women directors on CSR disclosure, which indicates that women on a board may improve CSR; board changes may provide necessary signals to investors indicating the potential for an improved firm image.
Keywords: board diversity; corporate governance; orporate social responsibility